2008
DOI: 10.1007/s10800-008-9668-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the electrochemical properties of intermediate temperature solid oxide fuel cells based on protonic and anionic electrolytes

Abstract: The physico-chemical properties of two protonic electrolytes BaCe 0.8 Y 0.2 O 3-d and BaCe 0.9 Y 0.1 O 3-d were investigated. The BaCe 0.8 Y 0.2 O 3-d electrolyte showed better crystallographic purity and lower amount of carbonate phase on the surface. A comparison between the BaCe 0.8 Y 0.2 O 3-d protonic electrolyte supported cell and an anionic (Ce 0.8 Gd 0.2 O 1.95 ) one was made. The maximum power densities (IR-free) of 183 mW cm -2 and 400 mW cm -2 were obtained in H 2 (R.H. 3%) at 700°C, for the protoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
(30 reference statements)
2
5
0
Order By: Relevance
“…A significant lower H 2 yield was recorded for the Ni/CGO compared to the alloyed compounds. This clearly indicates the catalytic promotion effect of the second transition element in the alloy towards ethanol conversion in accordance with the results reported in previous studies dealing with other low molecular weight hydrocarbons molecules [19][20][21][22][23] where Ni-Cu/CGO was essentially used as bulk anode.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A significant lower H 2 yield was recorded for the Ni/CGO compared to the alloyed compounds. This clearly indicates the catalytic promotion effect of the second transition element in the alloy towards ethanol conversion in accordance with the results reported in previous studies dealing with other low molecular weight hydrocarbons molecules [19][20][21][22][23] where Ni-Cu/CGO was essentially used as bulk anode.…”
Section: Resultssupporting
confidence: 91%
“…The physico-chemical behaviour and electrochemical performance of the Ni-based alloy/CGO systems for the direct utilization of ethanol are compared to the electrochemical performances of a bare. Previous studies have shown lower tolerance to carbon deposition of bulk Ni/CGO with respect to Ni-Cu/CGO during the direct utilization of dry hydrocarbons [19][20][21][22][23][24]. This confirms the need to avoid a large ensemble of pure Ni atoms as first catalytic layer in the presence of dry organic fuel feed.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, practical operation requires a pre-treatment of organic fuels to convert hydrocarbon and remove sulfur traces [ 4 ]. In parallel, the discovery of new materials and novel cell designs has allowed reducing the operating temperature to 600–800 °C [ 5 , 6 ]. Several studies have been concerned with the development of novel materials [ 7 , 8 ] and in particular novel anodes for advanced SOFCs operating in fuel-flexible mode [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…14) The activation energy of the proton conduction is typically in the range of 0.30.65 eV 58) and is lower than that of oxide ion conduction in solid oxides used for conventional SOFCs. Thus PCFC can work within intermediate temperature region (400600°C) which is lower than those of the conventional SOFCs based on a doped zirconia oxideion-conducting electrolyte.…”
Section: Introductionmentioning
confidence: 99%